(untitled) (The Agriculturists, 2018)
This study was conducted to examine the socio-economic condition, profitability, and marketing channel of small-scale private plant nurseries in Bangladesh. The study is based on survey data collected from 105 respondents from the Dhaka metropolitan area, Savar Upazila and two Upazilas of Gazipur District during January-March 2018 using a structured questionnaire. The study reveals that about 74 percent of private plant nursery established on government land in Dhaka metropolitan area, whereas in Gazipur and Savar areas the nurseries are mostly on the rented property which is 68 percent and 56 percent respectively. The average land size of the nursery is 9.06 decimal in Dhaka metropolitan area, 182.06 decimal in Gazipur and 121.18 decimal in Savar area. The average length of the business is 12 years where more than 80 percent of the firms are run by sole ownership. The average annual income using per decimal land from the plant nursery business is Tk.76,411 in Dhaka, Tk.7,066 in Gazipur and Tk.10,085 in Savar. The benefit-cost ratio is 1.53, 1.51 and 1.52 per decimal for Dhaka, Gazipur and Savar areas, respectively. Usually, two intermediaries such as wholesalers and retailers are involved in the plant nursery business. Although plant nursery business is a profitable enterprise, however, the owners are facing numerous problems which need to be improved in order to the smooth expansion of the nursery business in Bangladesh. The Agriculturists 2018; 16(2) 102-114